Isavuconazole for the Treatment of Invasive Mold Disease in Solid Organ Transplant Recipients: A Multicenter Study on Efficacy and Safety in Real-life Clinical Practice. Issue 3 (20th October 2022) - Fernández-Ruiz, Mario; Bodro, Marta; Gutiérrez Martín, Isabel; Rodriguez-Álvarez, Regino; Ruiz-Ruigómez, María; Sabé, Núria; López-Viñau, Teresa; Valerio, Maricela; Illaro, Aitziber; Fortún, Jesús; Salto-Alejandre, Sonsoles; Cordero, Elisa; et al.
Abstract : Background: Isavuconazole has theoretical advantages over other mold-active triazoles for the treatment of invasive aspergillosis and mucormycosis after solid organ transplantation (SOT). The available clinical experience, nevertheless, is scarce. Methods: We performed a retrospective study including all adult SOT recipients with proven or probable invasive mold disease (IMD) that received isavuconazole for ≥24 h as first-line or salvage therapy at 10 Spanish centers between September 2017 and November 2021. The primary efficacy outcome was clinical response (complete or partial resolution of attributable symptoms and findings) by weeks 6 and 12. Safety outcomes included the rates of treatment-emergent adverse events and premature isavuconazole discontinuation. Results: We included 81 SOT recipients that received isavuconazole for a median of 58.0 days because of invasive aspergillosis (n = 71) or mucormycosis (n = 10). Isavuconazole was used as first-line (72.8%) or salvage therapy due because of previous treatment-emergent toxicity (11.1%) or refractory IMD (7.4%). Combination therapy was common (37.0%), mainly with an echinocandin or liposomal amphotericin B. Clinical response by weeks 6 and 12 was achieved in 53.1% and 54.3% of patients, respectively, and was more likely when isavuconazole was administered as first-line single-agent therapy. At least 1 treatment-emergent adverse event occurred in 17.3% of patients, and 6.2% required premature discontinuation. Daily tacrolimus dose was reduced in two-thirds of patients by a median of 50.0%, although tacrolimus levels remained stable throughout the first month of therapy. Conclusions: Isavuconazole is a safe therapeutic option for IMD in SOT recipients, with efficacy comparable to other patient groups. Abstract :